Evaluasi Etika Profesi Advokat Dalam Pelayanan Hukum Dan Kepentingan Klien - Nurwandri, Andri; Syam, Nur Fadhilah; Ayu, Beby; Selvia, Mira; Hayati, Nur; Fadhillah, Rahmat; Santika, Windi (Pusdikra Publishing, 2023)
Advocate ethics are ethical guidelines for all advocates in Indonesia, but for advocates who are Muslim, they are bound by Islamic law, the source of which is the Al-Qur’an and Hadist, as the most important and highest guide to life above all else. The advocate profession is bound by a code of ethics in carrying out a profession emphasizes a formulation of good or bad advocate behavior on a formal legal basis, namely the clarity of the legitimate legal status of advocates. In a judicial system and professional organizations and or setting aside legal morals, namely a legal theory and legal philosophy which says that it can be used to require and or prohibit an advocate’s behavior based on a collective assessment of an advocate organization based on a code of ethics.